FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPUASAN PASIEN TERHADAP MUTU PELAYANAN KEPERAWATAN DI RSUD EMBUNG FATIMAH KOTA BATAM - Fasida Dharma Yudastoro; Mawardi Badar; Ditte Ayu Suntara (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Satisfaction can be defined as a feeling of satisfaction, joy and relief because someone consumes a product or service to obtain the services of a service. The sample in this study of 90 patients with inclusion criteria were respondents willing to sign a letter of approval to the respondents, patients in the general area of Regional General Hospital Embung Fatimah Batam, patients aged ≥ 20 years, patient bias read and write, and do not experience impaired cognitive function in critical condition. This study includes the type of analytical observational research with cross sectional design. In this cross-sectional approach in which the variables - variables that include the risk factors and variables - variables that include the effects of factors were observed simultaneously in the same time.The results of this study showed that of 90 patients, on the basis of five dimensions to measure the level of patient satisfaction that the results obtained from the dimensions of Being Real (Tangibles) most are generally satisfied (78%), of dimension reliability (Reliability) most are generally satisfied (67 %), of dimension Responsiveness (Responsiveness) most are generally satisfied (62%), Dimensions of Security Assurance Services (Assurance) most are generally satisfied (54%), of dimension Share Pain (Emphaty) most are generally satisfied (64%) the quality of nursing services at the Regional General Hospital Embung Fatimah Batam City. The results of this study is expected to be used as one source of information about problems, needs and desires of the patient's satisfaction and service as one of the proposed alternative solutions in an effort to improve patient satisfaction in the future.